Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.

Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Aminolysis of epoxides catalyzed by three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Catalysis, 2012)
The application of three-dimensional, mesoporous titanosilicates (Ti-SBA-12 and Ti-SBA-16) as reusable, solid catalysts for the synthesis of a range of beta-amino alcohols in high yields and selectivity through ring-opening of epoxides with amines at ambient and solvent-free conditions is reported, for the first time. These mesoporous titanosilicates (Si/Ti = 20-80) were prepared by a direct hydrothermal synthesis route adjusting the concentration of HCl (0.05-2 M) used in the synthesis. Ti ions in these catalysts were mostly substituted for Si in the framework. Water adsorption and Si-29 magic-angle spin nuclear magnetic resonance spectroscopy revealed that Ti-SBA-16 is more hydrophobic than Ti-SBA-12. Mesoporosity, three-dimensional architecture, surface hydrophobicity and easy access of Lewis acidic, framework-substituted Ti sites are the factors responsible for the superior activity of Ti-SBA-16 compared to Ti-SBA-12 and the hitherto known solid catalysts for this reaction. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Aminolysis of epoxides; beta-Amino alcohol; Mesoporous titanosilicates; Molecular sieves; Ring opening of epoxides with amines; Ti-SBA-12; Ti-SBA-16